Modelling and simulation of multi-input single-output DC power supply using single phase matrix converter (SPMC) / Mohd Shukri Mohd Ghazali ...[et al.] - Mohd Ghazali, Mohd Shukri; Mohd Zaki, Muhammad Zulsyahmie; Baharom, Rahimi; Abdullah, Nur Hidayah; Mohamad Rawi, Muhammad Shawwal (Universiti Teknologi MARA, 2021)
The multi-input converter is a power electronics device that has been used in various applications such as generating power by converting renewable energy, hybrid electric vehicle, and electronic equipment. This paper proposes a new circuit topology of Multi-Input Single-Output (MISO) DC power supply using Single-Phase Matrix Converter (SPMC). Compared to the typical circuit that uses at least two different circuits, the use of the proposed circuit topology only employed a single circuit to perform both rectifier and DC chopper operations. Two types of sources; AC and DC are connected to the input of the SPMC circuit. The SPMC switches will operate according to the integrated switching algorithms for AC to DC and DC to DC operations that are set by the controllers. The proposed circuit topology features the reduction of the number of components in the converter circuit, power losses, and circuit complexity, thus, improving the power density of the power supply system. A computer simulation of the proposed circuit has been designed and modeled using MATLAB/Simulink. The selected results are presented to verify the proposed system.